Teaching English Vocabulary in Junior High School Students by Using Simulation Games - Ghina Salsabila Wahab; Syamsu T; Lababa; Sam Hermansyah; Ernawati (International Journal of Sustainable Applied Sciences, 2023)
This study aimed to improve the English vocabulary of the Class Eight A students of SMP Negeri 5 Maritengngae by using Simulation Games.) With a population of 77 students from 3 classes, one class was selected where the Simulation Games were applied. The class which was selected was Class Eight A with 24 students which divided into10 boys and 14 girls. To collect the data, the researcher used tests and non-tests instrument. Tests instruments included pretest and post test and non-tests instruments included questionnaire and documentation. Because the research is mix study (qualitative and quantitative study), that’s why all the data that had been collected, were managed and explained by using quantitative and qualitative techniques. The students' responses were very good. This was shown by their responses to the statements in the questionnaire. There were 19 to 22 students or 79 % to 91.67 % students were Strongly Agree and Agree with the statements, such as: My English vocabulary increase after learning using Simulation Games, Simulation Games motivates me to learn, and so on. Because of the students’ responses were very good, automatically the students enjoyed using Simulation Games in the learning process. The impact of this was the students’ achievement were better after the application of Simulation Games.